Expression of Bone Morphogenetic Protein-2 forMeasuring Effectiveness of Freeze Dried Bovine Bone Xenografts (FDBBX) Biomaterials as Bone ConnectorMaterial - Agus Purnomo; Dhirgo Adji (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Osteogenic activity in normal fracture healing will start early at around 1 week after the repair , but not necessarily occur in fracture healing with the aid of grafts. Demineralized freeze dried bovine bone xenograft (DFDBBX) is a bone graft material made from cows that are widely produced recently to assist the process of bone grafting in humans, but has not been used on animals. It does not know how it works in helping to repair the bone. T wenty male SD rats weighing 150 g, were divided into 2 groups of 10 rats each. Group I was the control group, the rats were fractured and reconnected immediately using intramedullar pin fixation, Group II was a group of rats that were fractured and reconnected immediately using pin fixation intramedular plus graft material of freeze dried bovine bone xenograft. Fracture of the left femur was made in diaphysis part of bone. Evaluation of joints performed regularly at 1 week , 2 weeks, 4 weeks, 6 weeks and 8 weeks post surgery respectively by selecting at random, each group of 2 rats. Rats at each observation were collected two head / group, rats were then killed, the bone parts to be joined was taken and stored in 10% of formalin for histopathologic examination. Some pieces of the bones were used for the analysis of bone morphogenetic protein 2 (BMP-2 ) by immunohistochemical method. The results were then analyzed descriptively to see the changes directly on the X-rays and tissue. Overall results of this study showed that the graft material of DFDBBX were osteocondusive rather than osteoinductive properties. Nevertheless, the biomaterial is useful for orthopedic purposes primarily of handling cases with partial fracture of bone tissue which is lost. Due to the nature osteocondusive of DFDBBX will make cells to grow and to unify the separate bone fragments.Keywords : fracture, osteogenic activity , demineralized freeze dried bovine bone xenograft, bone morphogenetic protein-2, immunohistochemical analysis